Obinutuzumab-induced acute thrombocytopenia: a case report and literature review - Dou, Xuelin; Li, Kongyang; Lu, Jin (Frontiers in Oncology, 2024)
BackgroundObinutuzumab, a humanized type II anti-CD20 monoclonal antibody, is widely used in the treatment of B-cell lymphomas. Thrombocytopenia typically occurs 1 to 2 weeks after administration. In rare cases, obinutuzumab can induce severe acute thrombocytopenia within days of infusion, a condition known as “obinutuzumab-induced acute thrombocytopenia (OIAT).” Rituximab, a chimeric type I anti-CD20 monoclonal antibody, is also known to cause “rituximab-induced acute thrombocytopenia (RIAT).” This report presents a case of OIAT, with subsequent treatment switched to rituximab, which did not result in thrombocytopenia recurrence.Case PresentationA 38-year-old female patient with a 2-year history of lymphadenopathy was diagnosed with follicular lymphoma (Grade I-II). She was treated with obinutuzumab combined with bendamustine. Following the first administration of obinutuzumab, her platelet count dropped to 37×10⁹/L within 2 days and further declined to 27×10⁹/L on the fourth day without bleeding symptoms. The platelet count recovered by day 8. After a second obinutuzumab infusion, the platelet count again dropped to 15×10⁹/L within 1 day. Platelet transfusion was effective, and the count eventually recovered to 95×10⁹/L by day 29. No further acute thrombocytopenia occurred after switching to rituximab.ConclusionOIAT is a rare but serious adverse effect of obinutuzumab. This case highlights the importance of early recognition and monitoring of platelet counts in patients receiving obinutuzumab. The findings in our case, along with those in the literature, suggest that switching to rituximab or extending the interval before obinutuzumab re-administration can reduce the risk of recurrent thrombocytopenia. Further research is needed to elucidate the underlying mechanisms and establish treatment guidelines for OIAT.